THE EFFECT OF PERCEIVED ENJOYMENT ON INTENTION TO SHOP ONLINE (THE STUDY OF FACULTY OF ECONOMICS AND BUSINESS SAM RATULANGI UNIVERSITY MANADO) - Ulaan, Riska Valentine; Pangemanan, Sifrid S.; Lambey, Linda (FEB Universitas Sam Ratulangi Manado, 2016)
Online shopping is now become very popular in the world as it contributes a new way of purchase things. Young people tend to get a feeling of pleasure while doing their activity through internet such as browsing for a product via retailers? website. Once they get it, it will affect their intention to shop online. This research is aimed to know the effect of Perceived Enjoyment on Intention to Shop Online by applying Simple Regression Analysis. This method is to enable understanding the relationship between the independent variable (Perceived Enjoyment) and dependent variable (Intention to Shop Online). The result analysis indicated that Perceived Enjoyment has a positive influence on Intention to Shop Online. Furthermore, online shop owners must consider about the importance of consumers? feeling of pleasure while shopping through website. In this case, create an attractive web design so that it will attract consumers to do an online purchasing, because according to this study, when a consumer feels enjoy while doing their activity through internet, it will attract their intention to shop online. Keywords: perceived enjoyment, shop online, online shopping